A Checklist of Books By and About Canadian Artists in The Performing Arts/ Un Répertoire de Publications Sur ou Par les Artistes Canadians Dans les Arts Sceniques - Gardner, David (Theatre Research in Canada / Recherches théâtrales au Canada, 2001)
This ‘checklist’ of 248 books emerged out of a casual conversation with Martha Henry, while we were working together in 1998 on a production of The Crucible for the Manitoba Theatre Centre. Martha decried the paucity of books about Canadian performing artists, while I countered that we were now producing more and more every year. People, rather than theatres or analytic studies of drama, are the main focus of the checklist. I realize, as well, that there are several doubtful titles (books on Boris Karloff, Tyrone Guthrie and Henry Miller, for example), and purely theatrical readers may chafe at the inclusion of musicians, dancers, skaters, and bandleaders, but I was interested in documenting as many entertainment personalities as possible with viable Canadian connections. A section on unpublished works-in-progress is also included. There are bound to be errors and omissions in this preliminary (and primarily English) catalogue, and I would welcome corrections and/or additions at my e-mail address: david.gardner@utoronto.ca. L’idée de ce catalogue (de 248 livres) m’est venu après une conversation avec Martha Henry, alors que nous travaillons ensemble, en 1998, à une production de The Crucible au Manitoba Theatre Centre. Martha déplorait la pénurie de livres sur les artistes canadiens de la scène, et moi, je soutenais que nous en produisons de plus en plus chaque année. Ce sont les gens, plutôt que les théâtres ou les études analytiques sur le théâtre, qui sont au centre de cette liste. Je me rends compte aussi qu’y figurent quelques titres douteux (des livres sur Boris Karloff, Tyrone Guthrie et Henry Miller, par exemple) et les puristes de théâtre rechigneront peut-être au fait que j’ai compris des musiciens, des danseurs, des patineurs, et des chefs d’orchestre, mais j’ai cherché à documenter le plus grand nombre possible de personnalités du monde du spectacle, dans la mesure où leurs liens au Canada le justifiaient. On trouvera également une section relative aux travaux en cours. Il y aura inévitablement des erreurs et des omissions dans ce catalogue préliminaire (et essentiellement en anglais) et je serai reconnaissant de tout correction et/ou ajout via mon adresse courriel: david.gardner@utoronto.ca.